Effects of chronic realgar exposure on liver lipidome in mice and identification sensitive lipid biomarker model for realgar-induced liver damage. (1st January 2023) - Huo, Taoguang; Zhang, Weiwei; Yang, Jing; Li, Jian; Zhang, Yuwei; Guo, Haoqi; Wu, Xinyu; Li, Aihong; Feng, Cong; Jiang, Hong
Abstract: Chronic or excessive use of realgar induced liver damage. The biomarkers and exact mechanism have not been fully investigated. We performed an untargeted lipidomics study to investigate the effects of realgar on liver lipidome in mice and explore the sensitive biomarker model of realgar induced liver damage. It was found that realgar exposure induced arsenic accumulation in the liver, increased ROS generation, elevated MDA levels, decreased antioxidant enzymes levels, induced cell apoptosis, changed hepatocyte ultrastructure and morphology, and altered ALT, AST levels. Lipidomics study detected 30 classes and 1457 molecules in mice liver. The numbers of 49 and 103 lipid molecules were significantly altered ( FDR <0.05) in the livers of 0.45 g/kg and 1.35 g/kg realgar-exposed mice. The glycerophospholipid and sphingomyelin were the most affected lipid class. We focused on the effect of chronic realgar exposure on the mutual transformation of lipid subclasses and the fatty acid chain composition of lipids in mouse liver, and found that realgar affected the mutual transformation of PE-PC, PC-LPC and SM-Cer. Notably, we found that realgar exposure increased PUFAs linked phospholipids in mouse liver tissues. We identified two sensitive lipid molecules [PE (44:2p) and PE (16:0/22:5)] in combination can accurately distinguish and predict realgar induced liver damage, they are associated with oxidative damage and mitochondrial respiration in liver tissue. Our study provides an experimental basis for the mechanism research and early detection of realgar-induced liver damage. Graphical Abstract: ga1 Highlights: Chronic realgar exposure disturbed lipid metabolism in the mouse liver revealed by lipidomics. 1457 lipids were identified, and glycerophospholipid and sphingomyelin were the most affected. Chronic realgar exposure changed the mutual transformation of lipid classes. Chronic realgar exposure increased PUFAs linked phospholipids in mouse liver tissues. A sensitive lipid biomarker model involving two lipid molecules were developed.